Development of A Nursing Care Documentation Module Based on SDKI, SLKI, SIKI (3S) - Astutik, Emi Eliya; Budiman, M. Elyas Arif; Amrullah, Achmad Efrizal; Yuwanto, Mahmud Ady (Babali Publisher, 2025)
Backgroud: Nursing documentation is an important aspect of the nursing care workflow. Ineffective nursing documentation practices have been reported to negatively impact patient outcomes and health worker efficiency. Providing training for nurses will create positive attitudes and improve nurses' knowledge of nursing documentation. The purpose of this study was to determine the effectiveness of documentation training based on SDKI, SLKI and SIKI (3S) on the the quality of documentation of independent practice nurses. Method: The research design used in this study was a pre-experiment with a one group pre-test-post-test design. The population was independent practice nurses with a sample size of 63 nurses recruited using the total sampling technique. The instrument used is a checklist of nursing care documentation. The data analysis test uses the calculation of the Wilcoxon Paired test. Result: The results showed that the quality of nursing documentation before the intervention was in the less good category at 77.8% and the quality of documentation after the intervention was in the good category at 70.3%. Wilcoxon test results show a p value of 0.000 which indicates that there is an effect of documentation training based on SDKI, SLKI and SIKI (3S) on the quality of documentation of independent practice nurses. Conclusion: Nursing care documentation training helps improve documentation practices in the nurse's independent practice area and improve the quality of nursing services.